Evaluation of the Extension of Benign and Malignant Microcalcifications by Breast Magnetic Resonance Imaging, Mammography, and Ultrasonography - Tekcan Şanlı, Deniz Esin; Kayadibi, Yasemin; Yiğitoğlu, Neşe Uçar; Esmerer, Emel; Alay, Mustafa Tarık; Şanlı, Ahmet Necati (Cerrahpaşa Medical Journal, 2021)
Objective: The aim of this study was to compare the mammographic microcalcification areas with pathological enhancement in magnetic resonance imaging and heterogeneous areas in ultrasonography. Methods: Patients with microcalcification evaluated in the category of Breast Imaging Reporting and Data System (BI-RADS) 4-5 mammographically were examined by both ultrasonography and contrast-enhanced breast magnetic resonance imaging. The morphological type of microcalcifications by mammography, distribution pattern, and total distribution area were evaluated. The related imaging features with ultrasonography and distribution areas were evaluated. The area of the contrast-enhanced tissue, its distribution, enhancement kinetics (types 1, 2, and 3), and diffusion restriction were evaluated by magnetic resonance imaging. The widest dimensions of the pathological areas detected in all 3 examinations were statistically compared. Results: A total of 42 cases were included in the study. Although the most common mammographic microcalcification pattern in both groups was pleomorphic, it was significantly higher in the malignant group (P = .037). According to histopathological subtypes, the largest pathological area was seen in the invasive lobular carcinoma and invasive ductal carcinoma accompanyin with ductal carcinoma in situ. Although the sizes of malignant lesions on magnetic resonance imaging and ultrasonography were larger than benign ones, no significant difference was found (P > .05). There was a statistically significant moderate correlation between mammography and ultrasonography in showing both benign and malignant lesions, but no correlation was observed with magnetic resonance imaging (in benign lesions (P = 0.658, P = .004; in malignant lesions P = 0.519, P = .008). Conclusion: Contrast enhancement may not be seen with magnetic resonance imaging in low-grade or early-onset ductal carcinoma in situ cases; therefore, in the presence of suspicious sonomammographic findings, even if magnetic resonance imaging examination is negative, further histological evaluation should be performed. Cite this article as: Esin Tekcan Şanlı D, Kayadibi Y, Uçar Yiğitoğlu N, Esmerer E, Tarık Alay M, Necati Şanlı A. Evaluation of the extension of benign and malignant microcalcifications by breast MRI, mammography and ultrasonography. Cerrahpaşa Med J. 2021;45(3):197-204.